2005
DOI: 10.1063/1.2018799
|View full text |Cite
|
Sign up to set email alerts
|

Rotational line-integrated photoabsorption cross sections corresponding to the δ(,) band of NO:A molecular quantum-defect orbital procedure

Abstract: The rotational line-integrated photoabsorption cross sections corresponding to the delta(0,0) band of the nitric oxide (NO) molecule at 295 K, calculated with the molecular quantum-defect orbital methodology, are in rather good accord with the experimental measurements available in the literature. The achieved results are of straightforward use in atmospheric chemistry, such as in the assessment of the NO photodissociation rate constant, which is of great relevance for atmospheric modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This model‐potential approach has proved to be an adequate theoretical tool to supply quantitative values of spectral properties 18, 19 in recent applications that involved electronic and rovibronic transitions to molecular Rydberg states in a variety of molecular species. Recently, we have reported rotational intensities for the γ(0,0), δ(0,0), and δ(1,0) bands of NO 20–22. The present photoabsorption cross section calculations concerning this band at 295 K are, to our knowledge, the first theoretical data supplied.…”
Section: Introductionmentioning
confidence: 64%
“…This model‐potential approach has proved to be an adequate theoretical tool to supply quantitative values of spectral properties 18, 19 in recent applications that involved electronic and rovibronic transitions to molecular Rydberg states in a variety of molecular species. Recently, we have reported rotational intensities for the γ(0,0), δ(0,0), and δ(1,0) bands of NO 20–22. The present photoabsorption cross section calculations concerning this band at 295 K are, to our knowledge, the first theoretical data supplied.…”
Section: Introductionmentioning
confidence: 64%
“…[25] The study of the d bands of NO undergoes an important complication, as both are strongly perturbed by the presence of b bands, as Gadd et al [1991] have observed. In order to deal with this perturbation, in the calculation of the absorption cross sections of NO, we have followed the theoretical procedure developed by Galluser and Dressler [1982], already used in a previous study [Mayor et al, 2005b]. With the above procedure, the consequences of the mixing between the electronic states C and B, are expected to be correctly accounted for.…”
Section: Resultsmentioning
confidence: 99%
“…This methodology has proved, in a number of works [Velasco et al, 2003a[Velasco et al, , 2003bMayor et al, 2004Mayor et al, , 2005aBustos et al, 2004], to yield quantitative intensities for electronic transitions involving one or two Rydberg states. Very recently, rotational resolution has been accurately introduced in the procedure [Mayor et al, 2005b].…”
Section: Introductionmentioning
confidence: 99%
“…In a later work, Yoshino et al (2006) obtained ultrahigh-resolution cross-section measurements by using the combination of a VUV FT spectrometer and a synchrotron radiation source. Mayor et al (2005) calculated rotational line-integrated photoabsorption cross sections for the rotational lines of the C 2 Π(0)-X 2 Π(0) band with the Molecular Quantum Defect Orbital (MQDO) approach. Chauveau et al (2002) have calculated the absorption coefficient for spectral lines of the δ band system at different temperatures.…”
Section: Introductionmentioning
confidence: 99%